2015
DOI: 10.1007/s10571-015-0253-z
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Expression of Poly(rC)-Binding Protein PCBP2 Modulates Schwann Cell Proliferation After Sciatic Nerve Injury

Abstract: Poly(C)-binding proteins (PCBPs), also known as RNA-binding proteins, interact in a sequence-specific fashion with single-stranded poly(C). It was reported that PCBP2 contributed to gastric cancer proliferation and survival through miR-34a, and knockdown of PCBP2 inhibited glioma proliferation through inhibition of cell cycle progression. In addition, PCBP2 might play a critical role in the regulation of cortical neurons apoptosis induced by hypoxia or ischemia. Because of the essential role of PCBP2 in nervou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…In present study, a significant increase of LINC02535 and PCBP2 expression was found in CC tissues and cells compared with the adjacent normal tissues and normal cervical epithelial cells. Research has indicated that PCBP2 plays an important role in promoting the occurrence and development of many kinds of cancers (Chen et al, 2016;Tang, Gao, & Chen, 2015;Zhang et al, 2016). Through starBase website, there was a potential binding site between LINC02535 and PCBP2.…”
Section: Discussionmentioning
confidence: 99%
“…In present study, a significant increase of LINC02535 and PCBP2 expression was found in CC tissues and cells compared with the adjacent normal tissues and normal cervical epithelial cells. Research has indicated that PCBP2 plays an important role in promoting the occurrence and development of many kinds of cancers (Chen et al, 2016;Tang, Gao, & Chen, 2015;Zhang et al, 2016). Through starBase website, there was a potential binding site between LINC02535 and PCBP2.…”
Section: Discussionmentioning
confidence: 99%
“…Poly(C) binding protein 2 (PCBP2), a RNA-binding protein with 39 kDa, can regulate RNA stabilization, translational silencing and enhancement (Collier, Goobar-Larsson, Sokolowski, & Schwartz, 1998;Wan et al, 2016). It contains three K homology domains employed as the main RNA recognized regions (Chen et al, 2016;Leffers, Dejgaard, & Celis, 1995). Dysregulation of PCBP2 may damage multiple biological processes through RNAbinding pathways.…”
mentioning
confidence: 99%
“…Poly(rC) binding protein 2 (PCBP2), a 39 kDa protein, is a member of the a-globin mRNP stability complex [7,8]. As a generally known RNA-binding protein, PCBP2 possesses three K homology domains, which are the main RNA-recognition regions [9,10]. As a result of the RNA-binding characteristic, PCBP2 contributes to mRNA stabilization, translational silencing and enhancement [11,12].…”
mentioning
confidence: 99%